Adding composite truss to improve mechanical properties of reinforced concrete T-girder bridge. Issue 10 (July 2022) - Yang, Caiqian; Du, Wenping; Hou, Peng; Zhu, Fawang; Chen, Yaojing; Ma, Changjun; Pan, Yong; Zhang, Honglei
To solve the problem of insufficient transverse connection of T-girder bridges, this paper investigated the strengthening method of two composite trusses symmetrically installed in mid-span. The composite truss included two top plates, four diagonal braces, and one horizontal brace. An experimental investigation was carried out to study the mechanical properties of reinforced concrete T-girder using single-point loading method under four load cases. The experimental results showed that the maximum transverse stiffness of T-girder specimens strengthened with composite trusses improved by 12.4% compared with control beams. Simultaneously, it had an excellent restraining effect on the cracks development. The maximum percentage decrease in the deflection corresponding to the maximum load when the reinforced concrete T-girder strengthened with composite trusses over the control beam of up to 39.7 was observed. In addition, the load transverse distribution coefficient was investigated according to rigid-jointed slab (girder) method. The composite trusses were chosen as intermediate diaphragm to calculate moment of inertia. The analytical model was in an accurate with the experimental result under the same loading condition. The optimize spacing of composite trusses was given from 600 mm ( L /10) to 1200 mm ( L /5), and thickness of top plate was 30 mm when the load transverse distribution coefficient was homogeneously distributed. Finally, a three-dimensional finite element model was used to evaluate the effectiveness of composite trusses.